skip to main content

Puzzle ZIHG 

Please consider supporting BrainBashers [hide]

A Proof That 2 = 1:
let x=y:

           X = Y

multiply by x on both sides:

         X*X = XY

subtract y*y from both sides:

   X*X - Y*Y = XY - Y*Y


  (X+Y)(X-Y) = Y(X-Y)

divide by (x-y) on both sides:

       (X+Y) = Y

replace x with y:

         Y+Y = Y


          2Y = Y

divide by y on both sides:

           2 = 1

Where lies the flaw in the logic?

hide workings answer print

Share link:



Note: BrainBashers has a Dark Mode setting.